Accumulation of LDL/ox-LDL in the necrotic region participates in osteonecrosis of the femoral head: a pathological and in vitro study - Xin-Yuan Wang; Tian-Le Ma; Kang-Ning Chen; Zhi-Ying Pang; Hao Wang; Jun-Ming Huang; Guo-Bin Qi; Chen-Zhong Wang; Zeng-Xin Jiang; Lin-Jing Gong; Zhe Wang; Chang Jiang; et al. (Lipids in Health and Disease, 2021)
Abstract Background Osteonecrosis of the femoral head (ONFH) is a common but intractable disease that appears to involve lipid metabolic disorders. Although numerous studies have demonstrated that high blood levels of low-density lipoprotein (LDL) are closely associated with ONFH, there is limited evidence to explain the pathological role of LDL. Pathological and in vitro studies were performed to investigate the role of disordered metabolism of LDL and oxidized LDL (ox-LDL) in the femoral head in the pathology of ONFH. Methods Nineteen femoral head specimens from patients with ONFH were obtained for immunohistochemistry analysis. Murine long-bone osteocyte Y4 cells were used to study the effects of LDL/ox-LDL on cell viability, apoptosis, and metabolism process of LDL/ox-LDL in osteocytes in normoxic and hypoxic environments. Results In the pathological specimens, marked accumulation of LDL/ox-LDL was observed in osteocytes/lacunae of necrotic regions compared with healthy regions. In vitro studies showed that ox-LDL, rather than LDL, reduced the viability and enhanced apoptosis of osteocytes. Pathological sections indicated that the accumulation of ox-LDL was significantly associated with impaired blood supply. Exposure to a hypoxic environment appeared to be a key factor leading to LDL/ox-LDL accumulation by enhancing internalisation and oxidation of LDL in osteocytes. Conclusions The accumulation of LDL/ox-LDL in the necrotic region may contribute to the pathology of ONFH. These findings could provide new insights into the prevention and treatment of ONFH.